Behavior factors and characteristics of microbial vaginal flora related to the establishment of bacterial vaginosis in sex workers and non- sex - Simões, José A; Discacciati, Michelle G; Brolazo, Eliane; Portugal, Priscila M; Paupério, Rodrigo PS; Aroutcheva, Alla; Tao, V Lin (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: bacterial vaginosis is the most frequent cause of vaginal discharge in women in reproductive age. However, the causes that lead to this disorderare not completely known. Objective: evaluate the prevalence of bacterial vaginosis in sex workers and non-sex workers and the behavior al factors andcharacteristics of microbial vaginal flora related to the establishment of bacterial vaginosis. Methods: this cross-sectional study enrolled 68 women, 20 sexworkers and 48 non-sex workers (control group). The participants were submitted to gynecological examination, during which a cervico-vaginal specimenwas collected for vaginal pH, KOH test, Gram’s stain and culture for Gardnerella vaginalis, lactobaccilli and bacteriophages. For the statistical analysis, theOdds ratio with confidence interval of 95% and p value were performed. Results: the prevalence of BV was 60% among sex workers and 27% among controlgroup and this difference was statistically significant (OR= 4.04, CI 95% 1.19- 14.11). Vaginal douching, condom use, practices of anal and oral sex weresignificantly more frequent among sex workers (P<0.001). The frequency of Gardnerella vaginalis was higher among sex workers. On the other hand, adecrease recovery of lactobacilli and bacteriophages was found in sex workers compared in the control group. Conclusion: some behavior al factors andcharacteristics of microbial vaginal flora are associated with the higher prevalence of BV among sex workers.